Thermal energy aware proportionate scheduler for multiprocessor systems - Pasupuleti, Ramesh; Uppu, Ramachandraiah (International Journal of Engineering and Technology, 2018)
As per Mooreâ€™s law, the power consumption and heat solidity of the multiprocessor systems are increasing proportionately. High temperature increases the leakage power consumption of the processor and thus probably escort to thermal runaway. Efficiently managing the energy consumption of the multiprocessor systems in order to increase the battery lifetime is a major challenge in multiprocessor platforms. This article presents Thermal Energy aware proportionate scheduler (TEAPS) to reduce leakage power consumption. Simulation experiment illustrate that TEAPS reduces 16% of energy consumption with respect to Mixed Proportionate Fair (PFAIR-M) and 36% of energy consumption with respect to Proportionate Fair (PFAIR) Schedulers on the system consisting of 20 processors under full load condition.Â Â